Physicochemical Properties of Soil Ecosystem Polluted With Spent Engine Oil - Ebulue, Maximus M.; Ebulue, C. S. (Bumi Publikasi Nusantara, 2022)
Assessment of the possible impact of spent engine oil on the soil ecosystem is imperative for the determination of environmental acceptability. This study investigated this impact ex-situ using standard laboratory tools to determine the following parameters: pH, temperature, moisture content, and total petroleum hydrocarbon (TPH). The experiment demonstrated that at 1.0 – 3.5% contamination over time across days-zero to -28, spent engine oil upset the physicochemical equilibrium of the soil. A significantly reduced (p<0.05) pH in the range of 7.1 ± 0.00 to 6.2 ± 0.00 meant that the soil was acidic with a significant (p<0.05) increase in temperature from 33 ± 0.00 to 35.5 ± 0.03oC at increased concentrations overtime. The moisture content increased significantly (p<0.05) from 3.5 ± 0.00 to 19.31 ± 0.01% following the significant increase (p<0.05) in total petroleum hydrocarbon (TPH) from 0.002 ± 0.00 to 0.084 ± 0.00. This presupposed a hydrocarbon polluted soil ecosystem with oxygen deprivation; a demonstration of disturbed ecological equilibrium.